Market Structure and Conduct in Traditional Markets versus Modern Retail Stores in Situbondo Regency, Indonesia: Evidence from the Structure Conduct Performance (SCP) Framework - Muhammad Fakhrur Rizky; Agus Luthfi; Yulia Indrawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Modern retail expansion in Situbondo Regency has intensified competitive interaction with traditional markets, making it important to map differences in market structure, firm conduct, and performance outcomes. This study compares (i) market structure using concentration indicators (CR4 and the Herfindahl–Hirschman Index/HHI), (ii) competitive conduct (pricing practices, promotional intensity, service attributes, and relationship patterns), and (iii) performance proxies (sales turnover and selected price efficiency measures) within the SCP framework. The analysis applies a descriptive quantitative approach supported by targeted primary observations and questionnaire-based information, and complemented by official statistics and regulatory documents. Traditional-market samples include Panji, Besuki, and Panarukan markets, while modern-retail samples include local outlets of Indomaret, Alfamart, and Basmalah. Results indicate that traditional markets are relatively unconcentrated (CR4 = 38.0%; HHI = 744), consistent with a competitive structure dominated by many small vendors. Modern retail is more concentrated (CR4 = 77.0%; HHI = 1,644), suggesting moderate concentration and a tendency toward local oligopoly. Average monthly turnover per unit is higher for modern retail (IDR 36.36 million) than for traditional vendors (IDR 15.63 million). Price efficiency varies across commodities: some items show near parity, while several fresh commodities remain cheaper in traditional markets. Policy implications point to balanced local governance: zoning and permitting for modern stores, continuous revitalization of traditional markets, and strengthened MSME partnership schemes to ensure healthy and inclusive competition.